Editorial: Back to the Future-Predicting Possibilities in Open, Flexible, and Distance Learning - Maggie Hartnett; Niki Davis; Alison Fields (Flexible Learning Association of New Zealand, 2015)
In 2010 Ako Aotearoa, the national centre for tertiary teaching excellence, prompted DEANZ, our national association for open, flexible, and distance learning, to look towards the future in 2016. Reminiscent of the 1985 movie Back to the Future, the scenario set produced foresaw a range of practices in Aotearoa New Zealand. Papers in this issue describe and illustrate the scenario set and related trends. These include our increasing cultural diversity and adoption of social media to offer more learner-centred education that also increases engagement with employers, professions, and iwi. A review of Dron and Anderson's (2014) book supports our view of the trends and is recommended to readers.